Government spending composition, aggregate demand, growth and distribution - Daniele Tavani; Luca Zamparelli (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
We study a demand-driven growth and distribution model with a public sector, both without and with government debt. Government spending is used to finance the accumulation of public capital and to pay wages to public employees. The interaction between public capital and induced technical change makes long-run growth: (i) hump-shaped in the composition of government spending, (ii) wage-led, and (iii) government spending-led. Provided that the interest rate on government bonds is kept sufficiently below the growth rate, the size of government debt is irrelevant for long-run growth. – – Wir studieren ein Nachfrage-bestimmtes Wachstums- und Verteilungsmodell mit einem öffentlichen Sektor, sowohl mit als auch ohne Staatsschulden. Die Staatsausgaben finanzieren sowohl Akkumulation von öffentlichem Kapital als auch die Löhne von Staatsbediensteten. Die langfristige Wachstumsrate ist durch die Interaktion von technischem Fortschritt und öffentlichem Kapital (i) konkav je nach Zusammensetzung öffentlicher Ausgaben (ii) positiv von der Lohnquote und (iii) positiv vom Volumen der Staatsausgaben abhängig. Vorausgesetzt, dass der auf Staatsanleihen zu zahlende Zinssatz in ausreichendem Maße niedriger ist als die Wachstumsrate, hat die Höhe der Staatsschulden keinerlei Einfluss auf das langfristige Wachstum.
urn:nbn:de:101:1-201602195056
Keywords: E12; E25; E62; H50; 330; Keynesian growth; Government spending composition; Factor shares; Fiscal policy